(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The subject of the study of the proposed article is the drying up of the Aral Sea as a tragedy of the life and fate of the Karakalpak people. In addition, the emergence of the sea is gradually revealed, its invaluable benefits and services rendered to people in difficult times and the onset of devastation in Muynaka. The current sad state of the Aral Sea and the measures taken to improve its ecological condition.